The Implementation Of The Regional Cultural Preservation Policy Of Dharmasraya Regency - Tuanku Kerajaan, Sutan Riska; Koeswara, Hendri; Putera, Roni Ekha (Universitas Andalas, 2023)
This article analyzes and describes the implementation of the Regional Cultural Preservation Policy which is a form of effort to achieve the Vision and Mission of an Independent and Cultured Dharmasraya Maju Regency. The approach used in this study is a qualitative approach, and uses interview and documentation techniques, while the types of data consist of primary data and secondary data. The results of this study explain that the Regional Government of Dharmasraya Regency has formulated regional cultural problems by elaborating on regional strategic issues which then determines regional culture preservation strategies and regional policy directions. The implementation of the Regional Preservation Policy is carried out systematically and in collaboration with several relevant stakeholders such as LKAAM, DPRD, Ministry of Education, Culture, Research and Technology, Ministry of PUPR, BPCN, and BNPB.